Genetic analysis of the aquaporin water channels AQP12A and AQP12B in patients with chronic pancreatitis - Eiseler, Katharina; Dropmann, Lea Maria; Bugert, Peter; Ewers, Maren; Witt, Heiko (Pancreatology, 2022)
Background - Alterations in genes specifically expressed in the pancreas have been associated with chronic pancreatitis (CP). A significant percentage of patients with non-alcoholic CP, however, do not have mutations in known risk genes, suggesting the existence of further susceptibility genes. Four aquaporins are expressed in the exocrine pancreas: AQP1, AQP5, AQP8 and AQP12, the latter being found exclusively in this organ. Therefore, we investigated the two AQP12 genes, AQP12A and AQP12B, in CP patients. - Methods - We analyzed all exons and adjacent intronic regions of AQP12A and AQP12B in 292 German patients with non-alcoholic CP and 143 control subjects by direct DNA sequencing. - Results - In total, we discovered 41 non-synonymous changes, three of which were nonsense variants. Genotype and allele frequencies of these variants did not differ significantly between patients and controls (all p-values >0.05). Remarkably, we found a common nonsense variant in AQP12B, p.S152Tfs∗24, with an allele frequency of 15.7% in controls, including 2.8% homozygous subjects. This finding suggests that AQP12B is physiologically dispensable for normal pancreatic function. - Conclusions - Our results suggest that genetic alterations in AQP12A and AQP12B do not predispose to the development of non-alcoholic CP.